PENGARUH FILSAFAT NIETZSCHE TERHADAP PERKEMBANGAN FILSAFAT BARAT KONTEMPORER - Munir, Misnal (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2011)
Friedrich Wilhelm Nietzsche (October 15th, 1844 â August 25th, 1900) was a 19thÂ century German philosopher and classical philologist. He wrote critical texts on religion, morality, contemporary culture, philosophy and science which display a fondness for metaphor, irony and aphorism.Nietzsches philosophy remains a substantial influence within Western philosophy, notably existentialism and postmodernism. His style and radical questioning of value and objectivity of truth have resulted in commentaries andÂ interpretations, mostly in the continental tradition. His key ideas include the death of God, perspectivism, nihilism, the Ãbermensch, the eternal recurrence, and the will to power. His central philosophy is the idea of âlife-affirmationâ which involves a honest questioning of all doctrines that drain lifes expansive energies.Keywords: the death of God, perspectivism, nihilism, the Ãbermensch, existentialism and postmodernism.